2021
DOI: 10.3390/cancers13051051
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biodistribution and Efficacy Evaluation of NeoB, a Radiotracer Targeted to GRPR, in Mice Bearing Gastrointestinal Stromal Tumor

Abstract: NeoB is a radiotracer targeting the gastrin-releasing peptide receptor (GRPR), a G-protein–coupled receptor expressed in various cancers. The aim of the present study was to evaluate the biodistribution and efficacy of this new therapeutic agent in Gastrointestinal Stromal Tumors (GIST). Eighty-two SCID mice bearing GIST-882 tumors were employed. [177Lu]Lu-NeoB biodistribution was evaluated up to seven days by organ sampling (200 pmol/0.8 MBq, i.v.). For efficacy evaluation, mice received either saline, 400 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, no histopathological signs of continuous or severe pancreatic toxicity was observed. These findings are in agreement with the study by Montemagno et al (2021) who also reported no pancreatic alterations 100 days after mice bearing gastrointestinal stromal tumors were treated once weekly for 3 consecutive weeks with 37 MBq/400 pmol [ 177 Lu]Lu-NeoB [24].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, no histopathological signs of continuous or severe pancreatic toxicity was observed. These findings are in agreement with the study by Montemagno et al (2021) who also reported no pancreatic alterations 100 days after mice bearing gastrointestinal stromal tumors were treated once weekly for 3 consecutive weeks with 37 MBq/400 pmol [ 177 Lu]Lu-NeoB [24].…”
Section: Discussionsupporting
confidence: 93%
“…The therapeutic dosing regimen can still be optimized by potentially determining the number of doses needed to achieve a prolonged therapeutic effect and/or determining the intervals between doses, as the shorter half-life of 67 Cu compared to 177 Lu may allow for shorter treatment intervals. For example, a recent paper on [ 177 Lu]Lu-NeoB in animal models has proposed a weekly dose of 37 MBq for 3 weeks, which resulted in tumor inhibition in gastrointestinal stromal tumors (GIST) xenograft model [35].…”
Section: Discussionmentioning
confidence: 99%
“…78,79 recognized with increased GRPR, and emerging studies have investigated the possibility of targeted diagnosis and therapy using GRPR, such as in breast cancer, gastrointestinal cancer, colorectal cancer, and so on. [81][82][83] In OSCC, Lango et al have reported that GRPR expression was six times higher than that in normal tissues, and four times higher than that in adjacent normal epithelial tissues. 84 Furthermore, studies focusing on near-infrared fluorescent imaging of OSCC utilized GRPR targeting, and results showed that it's available in intraoperative surgical margin decision and metastatic lymph node detection.…”
Section: Mesenchymal-epithelial Transition Factor (C-met)mentioning
confidence: 99%